Evaluation of Bacterial Resistance to Antiseptics and Disinfectants in Clinical Isolates - Abdulrazaq, Luma N.; Khalaf, Ghada Nasrat; Obaid, Ahmed Nafia; Al-Gburi, Mayyadah Ali Ahmed; Abdulazez, Abdulsalam Abdulsattar (American Journal of Biology and Natural Sciences, 2026)
In this study 100 samples are collected from July 2021 to November 2021 from many hospitals in Anbar (Heet, Al- Ramadi and Haditha hospital). 59 sample isolates of Pseudomonas aeruginosa (P. aeruginosa) have been diagnosed from cases of infections of wounds and burns. There was different level of antibiotics resistance among bacterial isolates, the highest level of resistance was with meropenem 58 isolates (98.3%), followed by imipenem 52 isolates (88.1%), tobramycin and ofloxacin 51 isolates (86.4%), gentamycin 44 isolates (74.6%), ciprofloxacin 42 isolates (71.2%), amikacin 35 isolates (59.3%), ceftazidine 34 isolates (57.6%), cefotaxime 28 isolates (47.5%), and the lowest level of resistance was shown with ampicillin 16 isolates (27.1%). When studying the ability of P. aeruginosa isolates to secrete biofilm, as one of the virulence factors, was found all of these isolates (100%). During this study, three types of disinfectants were used as chemical agents that have a role such as anti-biofilm, and the lowest concentration used to inhibit biofilm production by bacterial isolates was measured. MICs were determined as 0.0031, 0.0062 and 0.0125 for povidone-iodine, IPC231 and surfaxn, respectively.